Cross talk between engulfment receptors stabilin-2 and integrin αvβ5 orchestrates engulfment of hosphatidylserine-exposed erythrocytes - 김소연; 박승윤; 김상엽; 배동준; 표재훈; 홍미나; 김인산 (American Society for Microbiology, 2012)
Efficient cell corpse clearance is critical for health in organisms. Apoptotic cells displaying phosphatidylserine (PS) are recognized by engulfment receptors and ingested through two conserved pathways. In one pathway, engulfment receptor brain-specific angiogenesis inhibitor 1 (BAI-1) or integrin functions upstream of ELMO/DOCK180 and activate the small GTPase Rac1. In the other pathway, engulfment receptor CED-1 or stabilin-2 acts in concert with the adaptor protein GULP to activate Rac1. Stabilin-2, a PS receptor, facilitates phagocytosis of apoptotic cells and mediates the production of anti-inflammatory cytokines. Here, we propose that the stabilin-2 extracellular domain consisting of integrin-binding fasciclin 1 (FAS1) domains coordinates the activities of the two phagocytic pathways via direct interactions with integrin. Interactions between stabilin-2 and integrin were determined using biochemical assays, including coimmunoprecipitation and fluorescence resonance energy transfer (FRET). These interactions appear to have functional relevance, since knockdown of endogenous alpha v beta 5 expression or treatment with a function-blocking alpha v beta 5 antibody significantly decreased stabilin-2-mediated phagocytosis in the absence of soluble factors. Our data collectively suggest that the engulfment receptors of the two phagocytic pathways communicate with each other to orchestrate engulfment of damaged erythrocytes. Coordinated phagocytic signaling would be advantageous for physiological and pathological circumstances that require rapid clearance of abnormal (apoptotic or aged) cells.